2015
DOI: 10.1177/0148607115570391
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Glutamine‐Enriched Nutrition Support for Patients With Severe Acute Pancreatitis

Abstract: Gln-enriched nutrition support is superior to conventional methods for SAP, and intravenous infusion may be a better choice for drug administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 24 publications
3
22
0
6
Order By: Relevance
“…This is thought to be due to the higher bioavailability of glutamine through parenteral administration, whereas enteral glutamine is used by the gut, therefore the immune system outside the gut would not have been affected by enteral glutamine supplementation. However, only one of the eight meta-analyses that performed a subgroup analysis on administration type presented a significant difference between parenteral and enteral administration, and this meta-analysis found that the length of stay in hospital was significantly shortened for the enteral route (4.5 days less for enteral vs. 2.5 days less for parenteral) (23). To confuse matters more, the only two meta-analyses on clinical studies that used enteral glutamine supplementation with critically ill patients demonstrated completely opposite effects on length of stay in hospital with one presenting a 4.73 day reduction and the other with a 0.19 day reduction (it should be noted that these two findings represent the two extremes from the 18 meta-analyses in this category) (24,32).…”
Section: Discussionmentioning
confidence: 89%
“…This is thought to be due to the higher bioavailability of glutamine through parenteral administration, whereas enteral glutamine is used by the gut, therefore the immune system outside the gut would not have been affected by enteral glutamine supplementation. However, only one of the eight meta-analyses that performed a subgroup analysis on administration type presented a significant difference between parenteral and enteral administration, and this meta-analysis found that the length of stay in hospital was significantly shortened for the enteral route (4.5 days less for enteral vs. 2.5 days less for parenteral) (23). To confuse matters more, the only two meta-analyses on clinical studies that used enteral glutamine supplementation with critically ill patients demonstrated completely opposite effects on length of stay in hospital with one presenting a 4.73 day reduction and the other with a 0.19 day reduction (it should be noted that these two findings represent the two extremes from the 18 meta-analyses in this category) (24,32).…”
Section: Discussionmentioning
confidence: 89%
“…Based on these findings, 8 TAs with the best‐quality evidence were selected for further analysis, as prioritized by points on rubric scores (Table ). They included cross‐disease malnutrition, sepsis, surgical complications, HACs, congestive heart failure, COPD, GI cancer, and pancreatitis …”
Section: Resultsmentioning
confidence: 99%
“…U usporedbi sa standardnom enteralnom potporom nadoknada glutamina rezultirala je kraćim boravkom u bolnici, sniženom incidencijom infektivnih komplikacija i mortaliteta, a intravenska nadoknada pokazala se boljim izborom zbog bolje bioraspoloživosti. 61 Što se tiče upalnih bolesti crijeva, Cochraneova sistematska analiza koja je obuhvatila samo dva RCT-a s ukupno 42 bolesnika zaključila je da nema dovoljno dokaza o učinkovitosti i sigurnosti glutamina u indukciji remisije pri Crohnovoj bolesti. 62…”
Section: Glutaminunclassified